Pengaruh Persepsi Masyarakat terhadap Keberhasilan Pengeloaan Dana Desa - Aiso Gusti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the influence of community perception on the success of village fund management, with a case study in Murjail Village. Village funds are an important instrument in supporting the development and welfare of village communities as mandated in Law Number 6 of 2014 concerning Villages. The success of village fund management is not only determined by administrative and technical aspects, but also by the perception of the community as beneficiaries. The research method used is a quantitative descriptive method with data collection techniques through questionnaires distributed to people aged 18 years and over. Of the 110 questionnaires issued, 99 of them were returned and analyzed. The results of the analysis show that there is a significant relationship between community perception (X) and the success of village fund management (Y) with a correlation coefficient value of 0.373 and a significance value (p-value) of 0.000 (<0.05). The coefficient of determination shows that community perception contributes 22.6% to the success of village fund management, while the rest is influenced by other factors. This finding shows the importance of building positive community perception in supporting the effectiveness of village fund management.